Successful treatment of methotrexate intolerance in juvenile idiopathic arthritis using eye movement desensitization and reprocessing - treatment protocol and preliminary results - Lea Höfel; Bruno Eppler; Magdalena Storf; Elizabeth Schnöbel-Müller; Johannes-Peter Haas; Boris Hügle (BMC, 2018)
Abstract Background Methotrexate (MTX), commonly used in juvenile idiopathic arthritis (JIA), frequently has to be discontinued due to intolerance with anticipatory and associative gastrointestinal adverse effects. Eye Movement Desensitization and Reprocessing (EMDR) is a psychological method where dysfunctional experiences and memories are reprocessed by recall combined with bilateral eye movements. The objective of this study was to assess efficacy of EMDR for treatment of MTX intolerance in JIA patients. Methods We performed an open prospective study on consecutive JIA patients with MTX intolerance. Intolerance was determined using the Methotrexate Intolerance Severity Score (MISS) questionnaire prior to treatment, directly after treatment and after four months. Health-related quality of life was determined using the PedsQL prior to and four months after treatment. Patients were treated according to an institutional EMDR protocol with 8 sessions over two weeks. Changes in MISS and PedsQL were analyzed using non-parametric statistics. Results Eighteen patients with MTX intolerance (median MISS at inclusion 16.5, IQR = 11.75-20.25) were included. Directly after treatment, MTX intolerance symptoms were significantly improved (median MISS 1 (IQR = 0-2). After four months, median MISS score was at 6.5 (IQR = 2.75-12.25, p = 0.001), with 9/18 patients showing MISS scores ≥6. Median PedsQL after 4 months improved significantly from 77.6% to 85.3% (p = 0.008). Conclusion MTX intolerance in children with JIA was effectively treated using an EMDR protocol, with lasting effect over a period of 4 months. EMDR treatment can potentially increase quality of life of affected patients and enable continued MTX treatment.